Analysis of Light Hydrocarbon (Ethane) Content in Propane Using the Boil off Gas System at the ABC LPG Terminal - Rahmadani, Rizki; Ardhiyanto, Nano Koes (Journal of Earth Energy Science, Engineering, and Technology, 2023)
LPG is a fuel that comes from refining petroleum or natural gas. Composed of various light hydrocarbons, LPG is one of the fuels with more environmentally friendly emissions than BBM. The ease with which light hydrocarbons in LPG evaporate causes problems such as increasing pressure in storage tanks during the landfill process. The use of the Boil-off Gas System is one of the systems used by ABC LPG Terminal to reduce evaporation loss in tanks due to high pressure. In this research, research was conducted on the effect of the inclusion of light hydrocarbons (ethane) in propane using the Boil-off Gas System. Based on the research results, the ethane content included in the propane at the ABC LPG Terminal exceeds the tolerance limit which affects the pressure in the propane drum condensate tank as a storage tank for the results of the BOG system, valve openings leading to flaring combustion and total losses in flaring. Using the Correlational Method supported by the Simple Linear Regression Test on data with a confidence level of 95% shows the effect of the relationship between ethane content and pressure in the propane drum condensate tank of 91.8%, valve opening to flaring combustion of 99.2% and total losses in flaring of 98.5%. It is classified as a powerful correlation relationship.